ASUHAN KEPERAWATAN PADA AN. A DENGAN DIARE DI WILAYAH RT 006 RW 007 KELURAHAN LIMO KOTA DEPOK - SITI ALYATUNNISA, (2023)
Background: From 2000 to 2018, diarrhea was the second-leading cause of death for kids under five worldwide. There are still 480,000 children under the age of five who die from diarrhea every year, even if the overall number of deaths among children under the age of five has reduced (UNICEF, 2020). Methods: This research used the nursing care case study method for child A with diarrhea in the RT area. 006 Rw. 007 Kelurahan Limo Depok City on 22-24 February 2023. Interviews, observations, physical examinations, and documentation were used to acquire the data. Results: Diarrhea connected to the infection process, Nutrition Deficit related to, and Knowledge Deficit related to lack of exposure to knowledge were the nursing diagnoses obtained. Nursing interventions carried out are the identification of causes of Diarrhea, identification of the history of feeding, monitoring colour, volume, frequency, and consistency of stools, recommending small and frequent meals in stages, recommend avoiding foods that are gas-forming, spicy, and contain lactose. Implementation of nursing following nursing interventions that have been made. The author has also implemented health education about risk factors for diarrheal disease and clean and healthy living behaviour and conducted nursing evaluations. Within 3x24 hours, the problem of Diarrhea can be resolved. Conclusion: The care that has been given to Child A based on nursing care can be resolved as evidenced by increased hand hygiene, increased body hygiene, increased appetite, and improved stool.